Analysis of phenolic and sensory characteristics of red wines under different terroir conditions in the eastern foothills of Helan mountains - WANG Zhangyu, HUANG Yongce, YANG Weiming, SHANG Hua, LAN Yibin, SHI Ying, DUAN Changqing, QI Mengyao (Zhongguo niangzao, 2024)
In order to investigate the effects of terroir conditions on phenolics and sensory quality of red wines, using 'Cabernet Sauvignon' and 'Marselan' red wines from three sub-regions in the eastern foothills of the Helan Mountains as the research objects, the phenolic composition profiles of red wine were analyzed by HPLC-MS/MS, and the two sensory characteristics, color and astringency, were investigated by combining the CIELAB color parameter and the artificial saliva precipitation index (ASPI). The results showed that the total contents of phenolics and the intensity of astringency of the red wines from the eastern foothills of the Helan Mountains as a whole showed a general trend of gradual increase from north to south, and that the red wines from the same sub-regions of 'Marselan' were darker in color, more saturated, and more astringent than those of 'Cabernet Sauvignon'. The phenolic content of Xixia wine samples was relatively low, the color of Yongning wine samples was relatively dark, and the astringency of Qingtongxia wine samples was strong. The percentage of high polymerization degree and the content of low polymerization tannins in red wines contributed significantly to their astringency intensity. The content of anthocyanin derivatives and the percentage of polymerized anthocyanins had a strong effect on the yellow hue (b* value) of wine samples. Different terroir conditions regulated the metabolism of flavonoids in grape berries and affected the phenolic profile of corresponding wines, but the effects of terroir factors on different grape varieties might be different.